The mathematical modeling for assessing the effectiveness of hot forging extruded round in plan forgings on crank presses - V. Telegin, I; M. Volodin, I; I. Zolotukhin, P (International Journal of Engineering and Technology, 2018)
The article presents the results of the development of a mathematical model for calculating the efficiency indices of technological schemes for hot volumetric stamping (GOSH) on crank hot-stamping presses (KGSHP) round in the forgings plan (for gear, pulley and other similar parts). Software solutions obtained on the basis of this model allow choosing from several variants of technological schemes the most effective for using it in production or further improvement.
Keywords: Hot Stamping; Metal Consumption; Billet; Forging.